PENERAPAN TEKNOLOGI PENGELOLAAN AIR DI RAWA LEBAK SEBAGAI USAHA PENINGKATAN INDEKS TANAM DI KABUPATEN MUARA ENIM - Djamhari, Sudaryanto (Jurnal Hidrosfir Indonesia, 2009)
Lebak bog farm (fresh water) potency in big enough Muara Enim District, South Sumatera, that is 12.684 hectare, what consist of 6.342 hectare shallow/superficial lebak, 3.805,2 hectare middle lebak, and 2.536,8hectare deep lebak. Lebak bog farm exploiting specially causeway lebak or skin-deep have constraint, that is newly can be exploited in the situation irrigate wet up to height of water ± 30 cm, is later then cultivated by other food crop or paddy while at dry condition cannot cultivate, with such condition of farm can only cultivate once plant in one year (IP 100 %). To overcome the above mentioned problem is way of which is gone through is by applying technology management of better water by making surjan rice field and constructively pump irrigating of problems of water can overcome, goodness when the rains and alsowhen dry season, so that lebak bog farm can be laboured by thrice planting in one year ( IP 300 %).